2018
DOI: 10.1249/mss.0000000000001439
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Skin Wettedness after Aerobic Training with and without Heat Acclimation

Abstract: A greater ωmax occurred after 8 wk of aerobic training, but ωmax was further augmented with heat acclimation, indicating only a partially increased heat loss capacity with training. These ωmax values may assist future predictions of heat stress risk in untrained/trained unacclimated individuals and trained heat-acclimated individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 33 publications
3
82
2
1
Order By: Relevance
“…Few studies have attempted to separate the effects of heat acclimation from aerobic fitness. A study by Ravanelli et al (2018) showed that a greater maximum skin wittedness occurred at the end of aerobic training in temperate conditions (22°C, 30% relative humidity), and this was further augmented by heat acclimation in a hot and humid condition (38°C, 65% relative humidity). This suggests that studies that include aerobic training in the heat acclimation/acclimatization protocols may have had their thermoregulatory effects augmented.…”
Section: Discussionmentioning
confidence: 98%
“…Few studies have attempted to separate the effects of heat acclimation from aerobic fitness. A study by Ravanelli et al (2018) showed that a greater maximum skin wittedness occurred at the end of aerobic training in temperate conditions (22°C, 30% relative humidity), and this was further augmented by heat acclimation in a hot and humid condition (38°C, 65% relative humidity). This suggests that studies that include aerobic training in the heat acclimation/acclimatization protocols may have had their thermoregulatory effects augmented.…”
Section: Discussionmentioning
confidence: 98%
“…For all subject, the total sweat rate or sweat Na + measured during the TT in cool conditions did not increase (from pre to post). This apparent lack of adaptation may be explained by testing in compensable conditions where sweating is dictated by the evaporative requirements (Ravanelli et al, 2018) and due to rapid alterations in the onset and decay of sweat sodium Na + (Williams et al, 1967; Armstrong and Maresh, 1991). Taken together with the lowered resting rectal temperature, these measures provide strong evidence that the participants were successfully acclimated following the prolonged heat training period.…”
Section: Discussionmentioning
confidence: 99%
“…With exercise training, there are increases in sweat output for the same T c increase, in addition to elevations in maximal sweat output ( Nadel et al, 1974 ; Henane et al, 1977 ; Roberts et al, 1977 ). Most recently, 8 weeks exercise training ( V̇ O 2 max increase from 46 to 52 ml/kg/min) increased local sweat rate, and thus skin wettedness from 72 to 85% surface area ( Ravanelli et al, 2018 ). The increased sweating function in the above studies may not be related to aerobic fitness per se , but more due to frequent and persistent rises in T c due to the training itself, evoking a mild heat adaptation ( Ravanelli et al, 2020 ).…”
Section: Aerobic Fitness and Trainingmentioning
confidence: 99%